English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Any ideas on how I'd solve this?

tanx(secx)^3/2

Thank you very much.

2007-02-10 05:30:33 · 5 answers · asked by other_user 2 in Science & Mathematics Mathematics

5 answers

(secx)^(3/2) i can write secx*(secx)^(1/2)
so int= mean integral
int tanx(secx)^(3/2)dx=
int tanxsecx(secx)^(1/2)dx

let u=secx
du=tanxsecxdx
so
int tanxsecx(secx)^(1/2)dx =
int u^(1/2)du
answer is (2/3)*u^(3/2)
but u=secx so put it back
answer is
(2/3)*(secx)^(3/2) +C
good luck

2007-02-10 05:51:18 · answer #1 · answered by Helper 6 · 0 0

Find the integral of tanx(secx)^(3/2).

First rearrange the terms to make it easier to integrate.

tanx(secx)^(3/2) = [tanx(secx)]√secx

Now we can integrate.

∫tanx(secx)^(3/2)dx
= ∫[tanx(secx)](√secx)dx
= (2/3)(secx)^(3/2) + C

2007-02-10 13:37:51 · answer #2 · answered by Northstar 7 · 0 1

INT { tanx(secx)^3/2 dx }

= INT { sec(x)^1/2 * sec(x) * tan(x) dx }

let y =sec(x)

=> dy = sec(x) * tan(x) * dx

Therefore, our integral becomes:

INT { y^1/2 * dy }

= { y^(3/2) } / (3/2) + C

= 2*sec(x)^(3/2) / 3 + C

2007-02-10 05:39:04 · answer #3 · answered by Anonymous · 0 0

a million) appropriate, enable us to regulate it extremely to envision if it turns appropriate right into a sprint greater advantageous sparkling. ? 5xe^(x^2) dx The 5 could be moved out, as that's a continuing multiplier. so: 5 ? xe^(x^2) dx So enable's basically concentration in this section: ? xe^(x^2) dx i'd use u-sub replace x^2 with u. Then du could be 2x dx. and you will simplify the needed that way. 2) Integration by utilising factors. you spot that there are 2 words, i'd have dv as 5^x and u as x^2 and you will bypass e out.

2016-11-03 02:08:22 · answer #4 · answered by ? 4 · 0 0

Integral ( tan(x) [sec(x)]^(3/2) dx )

Your first step is to decompose [sec(x)]^(3/2) into
[sec(x)]^(1/2) * sec(x)

Integral ( tan(x) [sec(x)]^(1/2) sec(x) dx )

Now, group the sec(x) and tan(x) together, next to the dx.

Integral ( [sec(x)]^(1/2) sec(x) tan(x) dx)

Here's where you use substitution.

Let u = sec(x). Then
du = sec(x) tan(x) dx {which is the tail end of our integral}. so our integral becomes

Integral ( u^(1/2) du)

Which is now easily integrable.

(2/3)u^(3/2) + C.

Substituting u = sec(x) back, we get

(2/3) [sec(x)]^(3/2) + C

2007-02-10 05:40:30 · answer #5 · answered by Puggy 7 · 0 0

fedest.com, questions and answers